Mechanical and Electronic Properties of Graphene Nanostructures - Faccio, Ricardo; Fernández-Werner, Luciana; Pardo, Helena; Goyenola, Cecilia; Denis, Pablo A.; Mombrú, Álvaro W. (IntechOpen, 2011)
None